The consumer right and protaction mechanism in Algeria and Malaysia ligislations: A comparative study in light of siasah syar'iyyah / Bahaeddine Megaache - Bahaeddine, Megaache (2017)
The core of this study deals with an important and sensitive issue which is the consumer. This issue has drawn the attention of the governmental and non governmental bodies, especially in light of the development and changes in today's world, the dominance of free economic system,the opening up of the global markets and the development of the production means which have increased the quantity and quality of products. This fact has prompted the states to enact new laws and regulations to provide more protection to the consumer and confront all the various risks that threaten his health and safety. Thus, we find both the Algerian and Malaysian legislators and other lawmakers are still issuing laws for consumer's protection regarding the technonological changes in the productive side that is submitted to the scientific development factor. The researcher has adapted the inductive, analytical and comparative method to conduct this study and identify some main points. First, to explain the consumer's protection policy in both Algerian and Malaysian legislations and to what extent are affected by the economic globalization factors. Second,to identify to how extent is that compatible with the islamic principles and its broad dimensions which include the five necessities and its impact in consumer's life in every place and time. Thirdly, how far is the islamic law flexible and the agreement of some new states made laws with its principles. Both the Algerian and Malaysian consumers live as the other consumers in a world that is subjected to a couple of variables in light of the economic globalization that is based on the commercial competition which is concerned as a new issue in the legislative credit of the new states laws as well as in a world that is controlled by a liberal economic system that produced.